Current Opportunities and Challenges in Biopolymer Thin Film Analysis—Determination of Film Thickness - Spirk, Stefan; Palasingh, Chonnipa; Nypelö, Tiina (Frontiers in Chemical Engineering, 2021)
Polymer thin films with thickness below 100 nm are a fascinating class of 2D materials with applications in many branches ranging from coatings to photoresists and insulating materials, to mention just a few. In recent years, the use of biopolymers extended the scope of polymer thin films with unique materials such as cellulose nanocrystals, cellulose nanofibrils or amorphous cellulose thin films, with tunable properties regarding their water uptake, particle size and optical behavior. The key information needed to optimize thin biopolymer films is governed by the film thickness which is often challenging to evaluate. Difficulties involve the presence of humidity as well as the soft and often heterogenous nature of the films. This minireview summarizes currently used methods and techniques for biopolymer thin film thickness analysis and outlines challenges for accurate and reproducible characterization.